Transnational regulatory networks: a study in compliance and legitimacy in counter-terrorist financing. Issue 3 (5th June 2020) - Goldbarsht, Doron; Harris, Hannah
Abstract : Purpose: This paper aims to explore the case of counter-terrorist financing (CTF) within the transnational regulatory network (TRN) of the Financial Action Task Force (FATF). The paper demonstrates how the structure and operation of the FATF reflect those of a TRN and shows how the FATF has been successful in securing formal compliance with CTF policies. Design/methodology/approach: The paper stresses that formal compliance does not guarantee actual compliance or effective enforcement. It is argued that the FATF and the CTF regime must balance concerns for legitimacy with those of flexibility and efficiency. Traditionally, TRNs have focused on flexibility, efficiency and informal cooperation over legitimacy. This paper demonstrates that legitimacy concerns cannot be ignored. Findings: A lack of legitimacy may ultimately result in non-compliance and ineffectiveness. On this basis, current efforts to build legitimacy through the FATF are noted but deemed insufficient. If this balance is not struck, the FATF may be doomed to failure through an overreliance on coercive methods. Particularly in the case of CTF, coercion is insufficient for meaningful compliance. Global enforcement by diverse states is a necessary condition for the success of the regime. Originality/value: This paper will fill the gaps existing in the literature by examining CTF, as well as the FATF as an example of TRN. This approach differs from other literature in the field, which deals solely with the effectiveness of the FATF and the global CTF without considering the effect of legitimacy on compliance.